The withdrawal of drugs from the market as a result of post-authorisation pharmacovigilance - Łukasz Dobrek (Polish Pharmaceutical Society, 2022)
Subject of study. Post-authorisation pharmacovigilance enables the continuous updating of knowledge about adverse effects of medicinal products used in everyday clinical practice. As a result, new information emerges that may change the current positive safety assessment of the drug and contributes to the withdrawal of the registered drug from the pharmaceutical market. Aim of study. The aim of the study was to review the decisions issued by the Chief Pharmaceutical Inspectorate in Poland in the period 2013-2021 on the withdrawal of a given medicinal product from the market as a result of post-authorisation pharmacovigilance and revealing significant adverse drug reactions. Material and methods. Publicly available decisions issued in the years 2013-2021 by the Chief Pharmaceutical Inspectorate, valid throughout the country, regarding the withdrawal of a given medicinal product from the pharmaceutical market were reviewed, with particular emphasis on decisions based on new information about the occurrence of significant adverse drug reactions Results. In the period 2013-2021, the inspectorate issued a total of 986 decisions and provisions, including only a few related to the permanent withdrawal of a given medicinal product from the pharmaceutical market, resulted from the disclosure of data changing the current safety assessment of a given drug. The vast majority of decisions to withdraw the drug from the market resulted from various qualitative and quantitative defects of a given medicinal product, incorrect labeling of the packaging, the presence of impurities or existing non-conformities in the content of Summary of Product Characteristics and leaflet and incorrect information placed on the outer packaging. The review revealed 12 pharmacologically active substances contained in preparations withdrawn by the inspectorate's decision due to the disclosure of significant adverse reactions in the post-authorization period. Conclusions. The examples of withdrawing medicinal products from the pharmaceutical market in Poland as well as in other EU countries and in the USA presented in the paper confirm the need for continuous safety supervision of drugs used in everyday clinical practice as part of the fourth, post-registration phase of clinical trials.